Teacher Assessment to School Readiness on the 5-6 Year-Old Children in State Kindergarten in Pekanbaru (Motoric Physical, Social Emotional, Moral, Language, and Cognitive Aspect) - Chairilsyah, Daviq; Kurnia, Rita (FKIP-Universitas Riau, 2018)
This research is to know teacher's assessment on school readinessfor children of 5-6 year-old in State Kindergarten in Pekanbaru (motoricphysical, emotional social, moral, language, and cognitive aspects). Thepopulation in this research is all children after 5-6 years with total of 425children and 150 children was taken as the sample. The method used isquantitative descriptive method. Data collection technique used wasobservation sheet. SBased on the results of data analysis, it was obtained thatthe percentage of all 5 aspects of school readiness in children aged 5-6 yearsin kindergarten in Pekanbaru: the aspect of physical motor readinessobtained equal to 68.22% belonging to high category of motoric physicalreadiness and smooth child is said Developing As Expectation (BSH),emotional social readiness aspect is obtained equal to 62.47% belong to highcategory hence emotional social readiness of child is said Develop AsExpectation (BSH), moral readiness aspect is obtained as much as 63.21%belongs to high category so the moral readiness of children is saidDeveloped As Expectation (BSH), the aspect of language readiness is51.14% is enough category then the readiness of children language is said toStart Developing (MB) and the aspect of cognitive readiness obtained by49.08% is sufficient then the cognitive readiness of children is said Startdeveloping (MB).